Learning from Community Practices: Social Capital of Farming Communities in Supporting Sustainable Agriculture - Widjayanthi, Lenny; Kusmiati, Ati; Ibanah, Indah; Agung, Sih; Wijayanto, Yagus; Wulanjani, Distiana; Prastowo, Sigit; Gabrillo, Christina A. (Newinera Publisher, 2024)
The use of chemical production facilities in farming, both food crops and horticultural crops, has an impact on agricultural land and human health, as well as causes damage to the environment, soil, water, air and living creatures. To achieve success in sustainable development, this is done by identifying social capital and developing farmer capacity. The research objectives are to identify sustainable agricultural practices carried out by farmers, identify community social capital in supporting sustainable agriculture. The research area was determined purposively in Pontang Village, Jember district. Determination of the research sample was carried out by simple random sampling on rice farmers. The research sample consisted of 106 respondents (margin of error of 10%). The data used in this research are primary and secondary data obtained from interviews, observations and document studies. Data analysis was carried out descriptively using scoring and categorization. Some sustainable agricultural practices carried out by communities in the research area are: organic agriculture, crop rotation and polyculture, soil management and agroforestry. Extension workers also conduct Field Schools (FS) for farmers. Farmers are given the knowledge and skills to utilize agricultural waste around them to make organic fertilizer. Extension workers also teach farmers in making PGPR, Beauveria bassiana, Pseudomonas fluorescens (Pf), Trichoderma, and planting refugia in rice fields. The social capital of the farming community in supporting sustainable agriculture is in the moderate category, as well as the supporting dimensions such as the social, norm and network dimension are also in the moderate category.